2023
DOI: 10.7759/cureus.42183
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Psychological Effects of Medically Supervised Fasting in Young Female Adults: An Observational Study

Pradeep MK,
Prakash B Kodali,
Gulab R Tewani
et al.

Abstract: Background Large-scale empirical and observational studies confirm the safety and efficacy of short-term intermittent fasting; however, prolonged fasting (fasting for more than two days or more) is not well studied. This study investigated the safety, physiological, and psychological effects of a medically supervised fasting (MSF) regimen on healthy volunteers. Methods In this observational study, 117 female participants with an average age of 21.02 (± 1.45) years underwent 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Earlier studies also reported MSF up to 10 days can improve the vitamin D levels. [11][12][13] A growing body of literature suggests the role of vitamin D in improving type 2 diabetes-related clinical outcomes by attenuating insulin resistance and priming the endocrine functions of the pancreas. 2,4,5 A meta-analysis study revealed the beneficial effect of vitamin D in reducing fasting blood sugar, glycated hemoglobin levels (HbA1C), and insulin resistance (HOMA-IR) in patients with diabetes mellitus and deficient vitamin D status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies also reported MSF up to 10 days can improve the vitamin D levels. [11][12][13] A growing body of literature suggests the role of vitamin D in improving type 2 diabetes-related clinical outcomes by attenuating insulin resistance and priming the endocrine functions of the pancreas. 2,4,5 A meta-analysis study revealed the beneficial effect of vitamin D in reducing fasting blood sugar, glycated hemoglobin levels (HbA1C), and insulin resistance (HOMA-IR) in patients with diabetes mellitus and deficient vitamin D status.…”
Section: Discussionmentioning
confidence: 99%
“…8 Therapeutic fasting has been shown to increase vitamin D levels in both healthy volunteers and chronic disease patients. [11][12][13] However, the role of therapeutic fasting in improving the vitamin D levels in T2DM patients is less understood. The present observational study is therefore intended to explore if the 10-day medically supervised fasting (MSF) has any potential impact on vitamin D, vitamin B12, fasting blood sugar levels, anthropometric measures, quality of life, and disease perception in T2DM patients.…”
Section: Introductionmentioning
confidence: 99%